2015
DOI: 10.1038/npp.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Thinning Affects Functional Connectivity and Regional Homogeneity of the Anterior Cingulate Cortex in Depression

Abstract: Major depressive disorder (MDD) is associated with structural and functional alterations in the prefrontal cortex (PFC) and anterior cingulate cortex (ACC). Enhanced ACC activity at rest (measured using various imaging methodologies) is found in treatment-responsive patients and is hypothesized to bolster treatment response by fostering adaptive rumination. However, whether structural changes influence functional coupling between fronto-cingulate regions and ACC regional homogeneity (ReHo) and whether these fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 58 publications
2
36
1
Order By: Relevance
“…The significant decrease in cortical thickness of BA24 and BA32 in MDD patients is partially consistent with the results of (Spati et al, 2015) who reported only one region of decreased cortical thickness in MDD - the right dorsal mid-anterior ACC. Similarly, reductions in thickness of the right rACC (Oertel-Knochel et al, 2015), the right dorsomedial PFC, including BA32 (Elvsashagen et al, 2013), and the left rACC (Foland-Ross et al, 2011; Lyoo et al, 2006) have been reported in patients with bipolar disorder.…”
Section: Discussionsupporting
confidence: 91%
“…The significant decrease in cortical thickness of BA24 and BA32 in MDD patients is partially consistent with the results of (Spati et al, 2015) who reported only one region of decreased cortical thickness in MDD - the right dorsal mid-anterior ACC. Similarly, reductions in thickness of the right rACC (Oertel-Knochel et al, 2015), the right dorsomedial PFC, including BA32 (Elvsashagen et al, 2013), and the left rACC (Foland-Ross et al, 2011; Lyoo et al, 2006) have been reported in patients with bipolar disorder.…”
Section: Discussionsupporting
confidence: 91%
“…Not surprisingly, given its importance to developmental psychopathology, connectivity of the ACC has been implicated in each of these research directions for depression (e.g. Barrett et al, 2004; Leaver et al, 2016; Spati et al, 2015). Research in this field could also, ultimately, identify new brain targets for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this hyperconnectivity is also associated with increased rumination (Spati et al , 2015). Further, graph theoretic metrics indicate that the dACC is more strongly integrated with and more centrally positioned among other nodes of depressed individuals’ neural networks (Onoda and Yamaguchi, 2015), suggesting that, in depression, networks are functionally organized to readily send salient information to other networks for further consolidation and goal modulation.…”
Section: Discussionmentioning
confidence: 99%